Why Great Britain`s success in Beijing could have been anticipated and why it should continue beyond 2012 - Nevill, A. M.; Balmer, N. J.; Winter, E. M. (British Journal of Sports Medicine, 2009)
Background: Home advantage in the summer Olympic Games is well known. What is not so well known is that countries that host the Olympic Games perform better in the games before and after the games in which they were hosts.